Correction to: Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth (Nano-Micro Letters, (2022), 14, 1, (63), 10.1007/s40820-022-00812-w) - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The original version of this article unfortunately contained some mistakes. The corrections are updated as follows:
CRIS-Team Scopus Importer:2022-06-03